Rational design, molecular docking and synthesis of novel homopiperazine linked imidazo[1, 2-a]pyrimidine derivatives as potent cytotoxic and antimicrobial agents. Issue 16 (15th August 2019) - Mantipally, Manohar; Gangireddy, Madhusudhana Reddy; Gundla, Rambabu; Badavath, Vishnu Nayak; Mandha, Santhosh Reddy; Maddipati, Venkatanarayana Chowdary
Graphical abstract: Highlights: Outstanding in vitro anticancer and antimicrobial activity. Compound 12 was found to be the most potent cytotoxic agent on A549 cells. Compound 10c displayed broad spectrum of antimicrobial activity against tested microbial stains. Molecular docking studies. Good yields. Abstract: Designed and synthesized novel homopiperazine linked imidazo[1, 2- a ]pyrimidine derivatives (10a–i, 11a–g, 12 ), and evaluated them for their in vitro cytotoxicity against HeLa cells (cervical cancer), A549 cells (lung cancer) cells, by MTT assay. Compound 12 (IC50  = 4.14 µM) and compound 10c (IC50  = 5.98 µM) were found to be 2.5 fold, and 1.74 fold more potent when compared with standard Etoposide (IC50  = 10.44 µM), against A549 (lung cancer cells). Compound 12 also found to be 1.57 and 1.13 fold potent against DU145 (IC50  = 6.24 µM) and HeLa (IC50  = 6.54 µM), respectively when compared with Etoposide (DU145, IC50  = 9.8 µM; HeLa, IC50  = 7.43 µM). Compound 10f (IC50  = 6.12 µM) was found to be 1.31 fold more potent than Etoposide (IC50  = 7.43 µM) against HeLa cell lines. Moreover compounds 10a and 11a showed cytotoxicity at low micro-molar concentrations against A549 cells. Synthesized compounds were also evaluated for their antimicrobial activity by Cup plate diffusion method. Compounds 10c, 11b, 11d and 11f displayed remarkable antimicrobial activity relating to their standard drugs Gentamycin, Amphotericin B and Ampicillin. Significantly, compound 10c showed broad spectrum activity against tested microbial strains. All the designed compounds were well occupied the binding site of the colchicine and interacted with both α- and β -tubuline interface (PDB ID: 3E22 ), which demonstrates that synthesized compounds are promising tubulin inhibitors. Also, the synthesized compounds occupied the catalytic triad and adenine-binding site, in the active site of β -ketoacyl-acyl carrier protein synthase III enzyme (PDB ID: 1MZS ). The molecular docking results provided the useful information for the future design of more potent inhibitors. These preliminary results convinced further investigation and modifications on synthesized compounds aiming towards the development of potential cytotoxic as well as antimicrobial agents.